TINDAK PERUNDUNGAN: BULLYING DI SEKOLAH DASAR DAN PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH DAN MENGATASINYA - Ridma Diana (Ilma Jurnal Pendidikan Islam, 2023)
This study examines the role of Islamic Religious Education teachers in preventing and overcoming bullying in one of the SDIT X in Senen District, Central Jakarta. This research uses descriptive skinative method. The data collection techniques used in this research are observation, interview and documentation. The resource persons in this research are all Islamic Religious Education teachers who have had a teaching period of 2 years at SDIT X, with a total of 4 Islamic Religious Education teachers. The data analysis techniques used in this research are data reduction, data presentation and inductive inference. The results showed that the forms of bullying that occurred at SDIT X were acts of bullying, bullying both in the form of verbal and physical. The role of Islamic Religious Education teachers in preventing and overcoming acts of bullying is done in several ways, such as 1) Islamic Religious Education teachers always provide exemplary examples of akhlakul karimah to students and continue to monitor the development of students in the school environment; 2) Islamic Religious Education teachers always relate the content of religious material learned to everyday life regarding good morals and attitudes; 3) Islamic Religious Education teachers call individually to students who commit acts of bullying, bullying and then advise and provide direction to the perpetrators and victims of bullying; 4) Islamic Religious Education teachers coordinate with homeroom teachers and school principals to follow up on acts of bullying, by calling the parents of the perpetrators and victims of bullying to find solutions and solve problems. Keywords: Bullying, Role of Islamic Religious Education Teacher, Elementary School